The validation of a new method that measures contact and flight times during vertical jump - Garcia-Lopez, J.; Peleteiro, J.; Rodriguez-Marroyo, J. A.; Morante, J. C.; Herrero, J. A.; Villa, J. G. (International Journal of Sports Medicine, 2005)
The aim of this study was to design and validate a vertical jump assessing system based on flight time measurements. Hence, the first phase of this study consisted of programming the software SportJumpv-1.0 and adapting a contact mat and a computer mouse in order to record the flight and contact times of a jump test. In the second phase, 9 subjects made 12 maximal and submaximal vertical single and rebound jumps. Thus 108 flight times and 36 contact times were simultaneously obtained with five different systems: ErgoJump Bosco System (PS), SportJump-v1.0 (SJ), Force Plate (FP), High-speed camera (HSC), and a Led (LED) filmed with a high-speed camera; FP was considered as the reference system. No significant differences were found either between SJ and LED, or between FP and HSC systems. SJ and LED overestimate flight time (9 ms and p < 0.001) and underestimate contact time in respect to FP values. PS underestimates flight time regarding FP values (4 ms and p < 0.01). In spite of the differences obtained between the systems, the errors found are constant. Those slightly depend on the subject's body mass for the systems that are connected to a contact mat. A high correlation between all of them was obtained (r ~ 1 and p < 0.001). The SJ system was validated for an accuracy of 500 Hz, and it was shown to be a useful tool in measuring flight and contact times during jumping. The differences and correlations found between the five systems show that it is necessary to take into account which system is being used when analyzing vertical jump performance.